FENOMENA PENGGEMAR DRAMA KOREA DI KALANGAN IBU-IBU RT 015 KELURAHAN CAKUNG TIMUR, JAKARTA TIMUR - Diestya Pristita Maharani (2021)
The society's enthusiasm for watching Korean dramas is getting bigger. This phenomenon was found in the neighborhood of RT 015, Kelurahan Cakung Timur, Jakarta Timur, which shows that among mothers are one of the demographics who show their enthusiasm in watching Korean dramas. Consumption of a popular culture through a media will produce a fan group that give a meaning to it till create a new identity. This research intended to find out the phenomenon of the existence of Korean drama in the society which more populer. Thus, this research's focused on explore the experiences of ten mothers in RT 015, Kelurahan Cakung Timur, East Jakarta in watching Korean dramas. By using the phenomenological method, this study will explain the concept of meaning and experience of subjects who have special characteristics. Regarding the method used by the researcher, the questions of this study are: 1) How do among mothers interpret Korean dramas?, 2) How do among mother's experience in watching Korean dramas?, 3) What are the motives behind the mothers watching Korean dramas? Through in-depth interviews conducted by ten mothers with an average duration of 20 to 55 minutes, the results of the study show that the themes obtained from Korean drama fans among the mothers of RT 015, Kelurahan Cakung Timur, are: society impact, discussion, mutual give recommendations, interest in actors, enjoy the drama, take for moral value, relieve the stress, not keep up with the development of the local entertainment, relate to everyday life, product procurement, keep pace with eating and Korean makeup on dramas